Analisis Efektivitas Pembelajaran Daring Dengan Pendekatan Kontekstual Terhadap Kemampuan Pemecahan Masalah Matematis - Siti Nur Millah; Ali Shodikin (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2021)
Abstract. Online learning is a technology learning model to complement face-to-face (direct) learning. It is hoped that students can still understand what the teacher says even though it is through online media. Learning challenges are a challenge for teachers so that the material can be conveyed properly, especially in the ability of students' mathematical problems. Mathematical problem skills are very useful for students, not only in solving math problems but also solving problems in everyday life. Problem ability is not something that is easily found by students so that students must train to develop this ability. For the ability to develop this, the learning process and strategy that is applied must be able to help understand the problem, plan for problem solving, find solutions and be able to conclude from solving the problem. One learning approach that can make students active in learning is the contextual approach. This experimental research aims to see the effectiveness of bold learning with a contextual approach to students' mathematical problem abilities. This study used a posttest only control group design. The population of this study were all students of class VIII MTs. Son and Daughter of Simo in the 2020/2021 school year. Through probability sampling techniques, classes VIII D and VIII G were selected as research samples. The research data were obtained from the mathematical problem ability test. The results showed that the most effective level in dealing with mathematical problems of students with a bold learning model with a contextual approach strategy was better than conventional learning. Keywords: Mathematical problem solving abilities, contextual approach, online learning. Abstrak. Pembelajaran daring atau online adalah salah satu model pembelajaran berteknologi untuk melengkapi pembelajaran tatap muka (langsung). Diharapkan siswa masih bisa memahami apa yang disampaikan oleh guru walaupun melalui media online. Pembelajaran daring menjadi tantangan tersendiri bagi guru agar materi bisa tersampaikan dengan baik utamanya dalam kemampuan pemecahan masalah matematis siswa. Kemampuan pemecahan masalah matematis sangat berguna bagi siswa, tidak hanya dalam memecahkan masalah matematika tapi juga memecahkan masalah dalam kehidupan sehari-hari. Kemampuan pemecahan masalah bukan merupakan suatu hal yang mudah didapati oleh siswa sehingga siswa harus melatih untuk mengembangkan kemampuan tersebut. Untuk mengembangkan kemampuan tersebut, maka proses dan strategi pembelajaran yang diterapkan haruslah dapat membantu siswa memahami masalah, merencanakan penyelesaian masalah, menemukan solusi dan dapat menarik kesimpulan dari penyelesaian masalah tersebut. Salah satu pendekatan pembelajaran yang dapat membuat siswa aktif dalam pembelajaran adalah pendekatan kontekstual. Penelitian eksperimen ini bertujuan untuk mengetahui efektivitas pembelajaran daring dengan pendekatan kontekstual terhadap kemampuan pemecahan masalah matematis siswa. Penelitian ini menggunakan posttest only control group design. Populasi penelitian ini adalah seluruh siswa kelas VIII MTs. Putra-Putri Simo tahun pelajaran 2020/2021. Melalui teknik probability sampling terpilih kelas VIII D dan VIII G sebagai sampel penelitian. Data penelitian diperoleh dari tes kemampuan pemecahan masalah matematis. Hasil penelitian ini menunjukkan bahwa tingkat efektivitas kemampuan pemecahan masalah matematis siswa model pembelajaran daring dengan strategi pendekatan kontekstual lebih baik dibandingkan dengan pembelajaran konvensional. Kata Kunci: Kemampuan pemecahan masalah matematis, pendekatan kontekstual, pembelajaran daring.